2010
DOI: 10.2190/cs.12.2.f
|View full text |Cite
|
Sign up to set email alerts
|

The Difference a Cohort Makes: Understanding Developmental Learning Communities in Community Colleges

Abstract: Learning communities, a small cohort of students enrolled together in two or more linked courses, have become a popular intervention to help underprepared students succeed in college. Though learning communities abound in practice, the key structural feature of a learning community-the cohortmay not be fully understood. Authors posit that a cohort needs both a structural and communal component to function well. This study examines qualitative data from a pilot site and four community colleges that participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…These findings are largely consistent with prior studies on learning communities, where academic gains are less common than changes in classroom climates and social support networks (Cerna et al 2008;Wathington, Pretlow III, and Mitchell 2010). However, there is evidence that learning communities enhance cognitive learning strategies, such as critical thinking and problem solving, for learning community students (Stefeanou and Galisbury-Glennon 2002).…”
Section: Spring 2015 and Fall 2015supporting
confidence: 88%
See 1 more Smart Citation
“…These findings are largely consistent with prior studies on learning communities, where academic gains are less common than changes in classroom climates and social support networks (Cerna et al 2008;Wathington, Pretlow III, and Mitchell 2010). However, there is evidence that learning communities enhance cognitive learning strategies, such as critical thinking and problem solving, for learning community students (Stefeanou and Galisbury-Glennon 2002).…”
Section: Spring 2015 and Fall 2015supporting
confidence: 88%
“…Regarding other outcomes at two-year postsecondary institutions, in a qualitative study, differences were discovered in classroom climates and academic support networks for students in learning communities versus students not in learning communities (Wathington, Pretlow III, and Mitchell 2010). Learning community students in Wathington, Pretlow III, and Mitchell's (2010) study generally reported more positive experiences at school than other students. The authors suggested that these experiences from learning communities were likely to result in increased student persistence.…”
Section: Two-year Institutionsmentioning
confidence: 95%
“…They used five community colleges across the United States where teachers and students participated in focus groups. Wathington et al (2011) found that students and faculty who were involved in learning communities felt they had a more supportive relationship than the students and teachers who were not in any such cohort.…”
Section: Services and Programsmentioning
confidence: 97%
“…In fact, many of the studies conducted on Black men during the last two decades have been concerned with why this student population was not academically successful (Costner et al, 2010;Cross & Slater, 2000;Iverson & Jaggers, 2015;Watkins, Green, Goodson, Guidry, & Stanley, 2007). These types of studies created a negative perception of the participants.…”
Section: Rationale For Using This Theorymentioning
confidence: 99%
See 1 more Smart Citation